PENGARUH PRODUKSI PERUSAHAAN TAMBANG NIKEL TERHADAP KONDISI EKONOMI MASYARAKAT DESA LINGKAR TAMBANG KABUPATEN KONAWE SELATAN (Studi Pada PT. Sambas Minerals Mining) - Irfan Ido; Jahidin Jahidin; Catria AS (Journal Publicuho, 2019)
The purpose of this study was to determine the effect of mining company production on the economic conditions of the community and how the population growth of Koeono Village and Watudemba Village (Mine Circle). The method of determining the sample in this study is Simple Random Sampling. The analytical method used to determine the growth rate of the economic condition of the community is carried out using quantitative descriptive analysis, while to determine the effect of nickel mining company production on economic conditions simple linear regression analysis is used. The results of the research on the economic conditions of the people of Koeono Village and Watudemba Village (Mine Circle) and simple linear regression revealed that nickel mining production had no effect on aspects of community income opportunities, employment opportunities, business opportunities, health, education and lifestyle because the value was far larger than the probability value where the probability value used is 0.05.